The social impact of the telecentre near community libraries under the perspective of the beneficiary: the Chico Mendes’ case - Marques, Helena de Almeida Pereira (2014)
This is a case study carried both in the Telecentre Chico Mendes and in the Chico Mendes Community Library, located in Porto Alegre/RS. The main goal was to investigate the beneficiaries’ perspective and their perception of social inclusion considering the use of these places. This study used a qualitative research with structured interviews in order to collect data of a due context. As a result the fact that both community programs are contiguous open doors for the uses of their facilities by beneficiaries. It can beinferred that the research participants could realize they are socially included, valued and privileged to have these environments so close to their community. Hence, the study concludes that the beneficiaries perceive the Telecentre and the Chico Mendes Community Library a space of integration, socialization and social inclusion. This work ends up suggesting actions to be performed in telecentres and community libraries.